A New Technique in Primary Repair of Congenital Esophageal Atresia Preventing Anastomotic Stricture Formation and Describing the Opening Condition of Blind Pouch: Plus (“+”) Incision - Mehmet Melek; Ufuk Cobanoglu (Gastroenterology Research and Practice)
Anastomotic strictures are common and important problems following repair procedures of esophageal atresia. We hereby defined an anastomosis technique that could efficiently prevent this complication in 11 patients with esophageal atresia (EA) and tracheoesophageal fistula (TEF). The proximal end of the atretic esophagus was opened with a plus (“+”)-shaped incision providing sufficient anastomosis width. Longitudinal incisions of 2 mm length were made on the anterior and posterior parts of the distal end according to the patients. The two ends were anastomosed with a primary suture at a single plain. We performed this technique on 11 patients, and in the 4-year follow-up period no dilatation proved necessary in any of our patients due to anastomotic strictures or symptomatic dysphagia. This technique that we have described provides a large zigzag anastomosis line and in this way minimizes the incidence of stricture formation. Furthermore, this technique, which we believe to have provided a new opinion on the topic of how to open the proximal end of an atretic esophagus, is quite easy and effective.